Analisis Semiotik Poligami Roland Barthes Pada Film Surga Yang Tak Dirindukan - Widodo, Anton; Rachman, Evy Septiyana (FDIK IAIN Padangsidimpuan, 2021)
Â This research is a research that puts forward the interpretation of a film produced by MD Pictures, MD Entertainment with the title Heaven that is not Missed. Furthermore, this research activity uses a qualitative method with Roland Barthes' semiotic theory as the blade of analysis. Analysis of the data in this study is to use Roland Barthes' semiotic analysis, which is to analyze every scene in the film Heaven that is Not Missed for interpretation and know its connotative and denotative meanings. The result of this research is that the film Heaven that is not missed about polygamy is that you have to learn to accept and be patient, because when someone is sincere and patient, the mind in someone can think clearly and can find a way out, but if we are burned by anger and recklessly take decision, we might even fall deeper and regret what we did later. The film Heaven that is not missed is actually a Da'wah film that is packaged in an interesting way to attract mad'u (audience). In the world of da'wah, preaching using the media is now a new alternative to convey the message of da'wah, but the delivery of da'wah messages must also be read carefully who is mad'u or the audience who will see it, because the film Heaven that is Not Missed becomes a religious film when the viewer sees it. a Muslim, but whether it is interpreted the same when the person watching is a non-Muslim, it does not rule out that the film depicts that Islam is unfair in treating women